SISTEM INFORMASI PEMBUATAN SURAT REKOM PINDAH NIKAH BERBASIS WEBSITE - Yua Isman Islam; Naufal Arif Maulana; Nur Azise (Jurnal Riset Sistem Informasi, 2025)
The Website-Based Marriage Status Change Recommendation Letter Information System is developed to simplify the process of creating recommendation letters for couples who wish to change their marital status with the relevant authorities. The primary goal of this application is to streamline a complex process, accelerate letter issuance, and make it easier for users to submit applications online. Key features include personal data entry, uploading supporting documents, and verification by authorized officers. With a web-based platform, this application can be accessed anytime and anywhere, reducing the need to visit government offices in person. The system is expected to make the administrative process related to marriage status changes more efficient and transparent.